Drug discrimination under concurrent variable-ratio variable-ratio schedules. - McMillan, D E (2002)
Pigeons were trained to discriminate 5 mg/kg pentobarbital from saline under concurrent variable-ratio (VR) VR schedules, in which responses on the pentobarbital-biased lever were reinforced under the VR schedule with the smaller response requirements when pentobarbital was given before the session, and responses on the saline-biased key were reinforced under the VR schedule with the larger response requirements. When saline was administered before the session, the reinforcement contingencies associated with the two response keys were reversed. When responding stabilized under concurrent VR 20 VR 30, concurrent VR 10 VR 40, or concurrent VR 5 VR 50 schedules, pigeons responded almost exclusively on the key on which fewer responses were required to produce the reinforcer. When other doses of pentobarbital and other drugs were substituted for the training dose, low doses of all drugs produced responding on the saline-biased key. Higher doses of pentobarbital and chlordiazepoxide produced responding only on the pentobarbital-biased key, whereas higher doses of ethanol and phencyclidine produced responding only on this key less often. d-Amphetamine produced responding primarily on the saline-biased key. When drugs generalized to pentobarbital, the shape of the generalization curve under concurrent VR VR schedules was more often graded than quantal in shape. Thus, drug discrimination can be established under concurrent VR VR schedules, but the shapes of drug-discrimination dose-response curves under concurrent VR VR schedules more closely resemble those seen under interval schedules than those seen under fixed-ratio schedules. Graded dose-response curves under concurrent VR VR schedules may relate to probability matching and difficulty in discriminating differences in reinforcement frequency.